ANALYSIS OF THE DETERMINANTS OF EXPORTING INTENSITY IN THE FI ELD OF INNOVATION - Suárez-Porto, Vanessa; Guisado-González, Manuel (Investigaciones Europeas de Dirección y Economía de la Empresa, 2014)

(untitled)
From a sample of Spanish manufacturing businesses, extracted from the 2005 Technological InnovationPanel (PITEC 2005), we suggest a lineal regression model in which we relate the exporting intensity withthe product innovation, the process innovation, the sectorial technological intensity, the business extentand the membership to a pool of businesses. In the descriptive and statistical analysis, we obtained thatall of these variables have a positive and significant influence on the exporting intensity. Regarding thismatter, we have checked that the main influence corresponds to businesses that develop product inno-vation strategies, are of medium extent, are assigned to sectors of medium-high technological intensityand belong to a foreign corporate group.